The Dissolution of the Cognitive Empire: Brazilian Street Art During the Pandemic and the Urban Landscape as a Medium for Decolonial Poetics (Alternautas, 2023)
This article discusses the urban art actions implemented during the pandemic in Brazil and their relationship with the decolonial turn in the arts. By examining examples such as the project Voices Against Racism and the CURA (Urban Art Circuit), which carried out numerous artistic-urban interventions in Brazilian cities involving Afro-descendant and Indigenous curators and artists, we propose a reflection on how urban spaces can enhance the city as a site of visibility and affirmation for marginalised groups and the political struggle in Latin American countries. With the closure of museums and other cultural institutions during the pandemic, cities became the epicentre of artistic and political expression. This coincided with the emergence of the decolonial movement in Brazilian arts and the social movements that fought against the obscurantist regime of the extreme-right government led by former President Jair Bolsonaro. While urban art has been traditionally analysed from the perspectives of art theories and cultural studies (e.g., through discussions on the divisions between the cult, the popular, and the mass), we argue that contemporary analyses require new parameters for an effective approach to this phenomenon, bringing together Latin-American studies and decolonial perspectives. Therefore, this study's primary objective is to significantly contribute to urban art studies by comprehensively understanding the city and its spaces of collectivisation as inherently transformative agents for fostering social change through artistic endeavours.